(3JYde GddZGJ GdCLfHjI aj eOjfI UjOG, hCKQg aj JfejI TNUjI GdJdGePI aj GdMdbI GdKGfjI ef GdJYdje GdCSGSjs - (3TfGYI, YdjG eMehOs ((3HjQhJs (3LGeYI GdbOjS jhSas, 2005)
(3JgOa gPg GdOQGSI Edi JHjGf hGbY JYde GddZGJ GdCLfHjI aj eOjfI UjOG hPdc dLgI CgOGa JYdegG hJfhYgG hGdJaGhJ GdMGUd aj GdefgL GdeJHY ef bHd GdbWGYGJ GdeNJdaI(B. (3heOi JaGYd JdGePI fgGjI GdMdbI GdKGfjI ef GdJYdje GdCSGSj eY cd eG JMedg gPg GddZGJ ef KbGaI, heaGgje hbje, heG JfWhj Ydjg ef NUhUjI, hbjeI eQOhO JYdegG aj TNUjGJge hCKQg hLOGfjkG hYbdjkG hMQcjkG(B. (3ceG JgOa Edi GdJYQa Ydi GdegGQGJ hGdeYGQa hGdbje GdJj jcJSHgG GdJdejP ef JYdeg GddZI GdCLfHjI ebGQfI eY eG jcJSHg ef JYde GddZI GdYQHjI(B. (3aj eYGdLI GdOQGSI, Je GSJNOGe GdefgL GdhUaj dCgejJg aj eKd gPg GdOQGSGJ(B. (3CeG ajeG jNU YjfI GdOQGSI, abO JhRYJ Ydi (B15 (3eOQSI ef CUd (B26 (3eOQSI GHJOGFjI aj efWbI UjOG, GdJj TedJ (B412 (3WGdkHG ef WdGH GdUa GdSGOS GdCSGSj ef GdLfSjf, GdJj JYJeO GddZI GdEfLdjRjI Ch GdaQfSjI cdZI CLfHjI CSGSjI aj GdbWGYjf GdQSej hGdNGU, ceG TedJ GdYjfI YOkOG ef GdeSDhdjf GdJQHhjjf, h(B48 (3aQOkG ef GdeYdejf, cPdc GNJjQJ YThGFjkG YjfI ef GdCgGdj, hYjfI ef cJH GddZI GdCLfHjI hGdYQHjI GdeYJeOI aj GdeOGQS(B. (3dLeY GdeYdheGJ JfhYJ GdCOhGJ dJTed(B: 1) (3ebGHdI eY GdeSDhdjf, (B2) (3ESJeGQI ddeOjQjf, (B3) (3ESJeGQI GdeYde, (B4) (3ESJeGQI GdCgd, (B5) (3ESJeGQI GdJdejP(B. (3hHYO JMdjd GdHjGfGJ NdUJ GdOQGSI ddJhUd Edi eG jdj(B: 1) (3gfGc fSH YGdjI JTjQ Edi GcJSGH GdJdGePI ehGba EjLGHjI JLGg GddZI GdCLfHjI GdJj jJYdehfgG, cPdc GcJSGHge ddbOQGJ GdYbdjI, cGdJMdjd hGdEOQGc hGdage(B. 2) (3dJYdje GddZI GdCLfHjI HSf eHcQ, BKGQ EjLGHjI Ydi TNUjI GdJdejP(B. 3) (3ddcJGH GdeOQSj OhQ cHjQ HeG jJVefg ef eaGgje heYGQa aj Jchjf GJLGgGJ GdJdGePI hLPHge CcKQ ddcJGH (B4) (3CHOJ GdEfGK hHfSH YGdjI Cfgf CcKQ JLGhHkG hbGHdjI eY GdJWhQ hGdJZjjQ(B. 5) (3gfGc OdGdGJ hGVMI Ydi Cf JCKjQ JYde GddZGJ GdCLfHjI aj TNUjI GdJdejP jHbi eMOhOkG, EP eG Je aj HjFI JaJbQ Edi GdJLgjRGJ GdJQHhjI GdeJWhQI, hEdi GdhSGFd GdJYdjejI GddGReI(B.s
(3GdfhY (B: (3CWQhMIs
Keywords: Cycle primaire Enseignement des langues; Elementary Education Teaching languages; (3GdeQMdI GdGHJOGFjI JYdje GddZGJs; (3UjOGs